KEWIRAUSAHAAN SYARIAH UNTUK KEMASLAHATAN BERSAMA - Soeharjoto Soeharjoto; Nirdukita Ratnawati; A. A. Hubur; Sumiyarti Sumiyarti; Wahyuningsih Santosa; Sisca Damayanti; Debbie Aryani Tribudhi (LP2M STP Mataram, 2023)
Indonesia has abundant natural and human resources that have the potential to become a developed country. However, all this has not made it a prosperous country. The digital era, provides many conveniences, thus changing the pattern of human life. The COVID-19 pandemic has accelerated students' maturity and mental development. This makes education managers and students increasingly realize how important it is to be an independent human being by being an entrepreneur. However, in order to accelerate the preparation and development of students' ability to become trustworthy entrepreneurs, it is necessary to collaborate with universities. This school which is oriented towards Islamic education, wants to develop a sharia entrepreneur. For that, the Islamic Entrepreneur Boarding School collaborates with the Faculty of Economics and Business Universitas Trisakti to carry out community service activities, in order to motivate students to become sharia entrepreneurs, who can provide mutual benefits. This activity is carried out using the extension method. Participants of this activities were representatives of groups of students from the school. Community service activities have been carried out well, because they can motivate and increase the knowledge and insight of students. Growing knowledge and insigh, not only from the conventional entrepreneurial side, but also from the sharia point of view that can increase mutual benefit.